2010
DOI: 10.1007/s00247-010-1912-3
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic high-flow priapism in children treated with autologous blood clot embolization: long-term results and review of the literature

Abstract: Selective arterial embolization with autologous clot achieved treatment for high-flow priapism in this study with 100% occlusion rate with a maximum of two sessions and no signs of erectile dysfunction were observed in any of the children during long-term follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…It often leads to either urethral injury [3,4] or arteriocavernosal fistula [5,6]. In our case, a patient had a bleeding at his urethral meatus after straddle injury.…”
Section: Discussionmentioning
confidence: 81%
“…It often leads to either urethral injury [3,4] or arteriocavernosal fistula [5,6]. In our case, a patient had a bleeding at his urethral meatus after straddle injury.…”
Section: Discussionmentioning
confidence: 81%
“…Also, no foreign body reactions that other embolisation materials cause during the process have been noted. In other studies conducted by our colleagues with larger patient sets the technique has been found to be 100% effective and no erectile dysfunction has been noted so far in any of the patients (Cantasdemir et al, ). In the literature, any side effects of autologous blood clot embolisation such as the formation of new fistulas have not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Autologous blood clot has been used as a temporary embolic agent, especially in endovascular interventions. It results in cicatricial closure of the fistula with subsequent recanalization of the embolized feeding artery . However, there has been no report of its application for percutaneous renal AVF or PA embolization.…”
Section: Discussionmentioning
confidence: 99%
“…It results in cicatricial closure of the fistula with subsequent recanalization of the embolized feeding artery. [5][6][7] However, there has been no report of its application for percutaneous renal AVF or PA embolization.…”
Section: Discussionmentioning
confidence: 99%